Assisting Women’s Farmer Community in Utilization of Coconut Water for Coconut Ketchup Production in Penggung, Hargorejo Kokap Kulon Progo - Della Rizki Damayanti; Mokhannad Zaeni Amin; Hanindya Rina Hanifah; Lukman Hakim Muzakky; Ratna Sari; Diki mandala; Sofia Nita; Jeklin Mandala; Anom Sarianingsih; Nur Ginanjar Karim (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2019)
Penggung, Hargorejo, Kokap, Kulon Progo is the region that has many growing coconut trees. The utilization of the coconut including the nira (fermented coconut) and coconut flesh. The coconut is extracted to get the coconut flesh while the coir and shell were sold to collectors. The water was wasted without utilization. In this case, Kelompok Wanita Tani (KWT or women’s farmer community) is trying to utilize coconut water through assisting the program of the coconut soy sauce production. The main material for making soy sauce is coconut water and spices. The method used by washed spices and mashed it, then warmed up the spices with coconut water. Because of the low protein content, the water soy sauce can be added with soybean, fish or shrimp powder to increase the protein. The water coconut soy sauce contained 24.01% of water, 2.30% protein, 6.09% of ash and 12.34% solid solution. The soy sauce lasts for a week without any preservatives. For more seven days usage can be added with 0.02% benzoate acid 0.5 g into a bottle of soy sauce.